Combustion behaviour of relatively large pulverised biomass particles at rapid heating rates - Mock, Chinsung; Lee, Hookyung; Choi, Sangmin; Manovic, Vasilije (American Chemical Society, 2016)
A pulverized solid fuel particle in a hot gas stream appears to have different characteristic behaviors at several stages, including heat-up, release of volatile matter, gas phase, and solid combustion. The characteristics of these stages may vary distinctly depending on devolatilization rate, the particle temperature history, and its chemical and physical properties. Biomass particles manifest different combustion behavior from that of burning coal particles under the same combustion conditions because they contain more volatiles (less fixed carbon), and they have a relatively lower particle density due to their fibrous structure. This paper presents an experimental study of burning behavior of different types of biomass particles (torrefied wood, coffee waste, and sewage sludge). The main experimental parameters—gas temperatures of 1090 and 1340 K, and O2 concentrations ranging from 10% to 40%—were employed to investigate the burning of biomass through a direct-observation approach using a high-speed photography technique at 7000 frames/s. In the case of firing/cofiring, biomass particles must be larger than the coal particles in order to achieve an equivalent thermal balance due to the higher energy density of coal. Therefore, the selected biomass samples were in the size range from 150–215 μm to 425–500 μm. The experimental setup has a cross-flow configuration for particle injection in order to enhance interaction between the particle and the two different streams—a cold carrier gas at 298 K, and upward-flowing postcombustion gases. It is believed that the employed experimental conditions are similar to those in a realistic furnace with a rapid heating rate of 105 K/s. The experimentally significant results, including the effective radii of the volatile flames, degrees of flame intensity, and the maximum size of a particle, are important for validation of models of single biomass particle combustion.